The 2-dimensional to 3-dimensional growth transition in Physcomitrium patens - Weeks, Z (2024)
Plants colonised the land around 470 million years ago. This was facilitated by the acquisition of apical cells capable of dividing in three dimensions, which allowed the development of complex 3-dimensional (3D) morphologies. This is in contrast to the charophyte green algae, from which land plants evolved, which have apical cells that can divide in only 1 or 2 dimensions. Therefore, 3D growth is a pivotal and unifying feature of all land plants, but we know little about how it is regulated. The model moss Physcomitrium patens has been developed as a model system in which to dissect the genetic basis of 3D growth, which also involves complex auxin-cytokinin crosstalk. Previously, a 3D-defective mutant named Ppnog1R was generated in a forward genetics screen. Ppnog1R exhibits cell division orientation defects that result in early developmental arrest of the 3D "shoots" and consequently a complete failure to establish 3D growth. Therefore, 3D growth in P. patens depends on the PpNOG1 gene, which encodes a protein with a ubiquitin-associated domain. In this work, the function of PpNOG1 was further clarified by genetic manipulation of the Ppnog1R mutant and analysis of the resulting phenotypes. To reveal genetic interactors of PpNOG1, a suppressor screen was performed using an independent nog1 mutant, which yielded two suppressor of nog1 mutants (snog1a and snog1b) with restored capacity for 3D growth. The causative mutation in snog1a was mapped and the PpSNOG1A gene was identified as an inhibitor of 3D growth and genetic antagonist of PpNOG1. PpSNOG1A also encodes a protein with a ubiquitin-associated domain. Finally, several RNA-seq experiments were performed, which allowed examination of the transcriptomic landscape of Ppnog1R, another 3D-defective mutant, Ppnog2R, and the snog1a suppressor mutant. These analyses revealed processes and pathways that have been impacted in these mutants.